1876 Iowa Acts 142, An Act to Diminish Liability to Railroad Accidents and to Punish Interference with, and Injury to the Property of Railroad Companies, chap. 148, § 1 - (:unkn) unknown (General Publisher, 1876)
Prohibited throwing stones, or other substance, or discharging any gun, pistol, or other firearm at any railroad train, car, or locomotive engine. Violators guilty of a misdemeanor.
--
Keywords: DISCHARGE